초고속 Real-time PCR을 이용한 Tomato yellow leaf curl virus의 신속진단 - 김택수(Tack-Soo Kim); 최승국(Seung-Kook Choi); 고민정(Min-jung Ko); 이민호(Minho Lee); 최형석(Hyung seok Choi); 이세원(Se-Weon Lee); 박경석(Kyungseok Park); 박진우(Jin-Woo Park) (Sigmulbyeong yeon'gu, 2012)
Tomato yellow leaf curl virus (TYLCV), transmitted exclusively by the whitefly (Bemisia tabaci) in a circulative manner is one of the most important virus in tomato. Since the first report of TYLCV incidence in Korea in 2008, the virus has rapidly spread nationwide. TYLCV currently causes serious economic losses in tomato production in Korea. Early detection of TYLCV is one of the most important methods to allow rouging of infected tomato plants to minimize the spread of TYLCV disease. We have developed an ultra-rapid and sensitive real-time polymerase chain reaction (PCR) using a new designed real-time PCR system, GenSpectorTM TMC-1000 that is a small and portable real-time PCR machine requiring only a $5μl$ reaction volume on microchips. The new system provides ultra-high speed reaction (30 cycles in less than 15 minutes) and melting curve analysis for amplified TYLCV products. These results suggest that the short reaction time and ultra sensitivity of the GenSpector$^{TM}$-based real-time PCR technique is suitable for monitoring epidemics and pre-pandemic TYLCV disease. This is the first report for plant virus detection using an ultra-rapid real-time PCR system. 토마토황화잎말림바이러스(Tomato yellow leaf curl virus; TYLCV)는 온실가루이(Bemisia tabaci)에 의해서 영속전염되는 DNA 바이러스로 토마토에 발생하는 가장 중요한 병 중 하나이다. 우리나라에서 TYLCV는 2008년 최초로 보고된 이래 급속하게 전국적으로 확산되어 토마토 생산에 심각한 경제적 손실을 일으키고 있다. 토마토 생산과정에서 TYLCV의 확산을 최소화하기 위해 바이러스의 조기진단이 매우 중요하다. 본 연구에서는 바이러스의 신속진단을 위해 초고속 정밀 PCR 진단기술을 개발하였으며, 이는 마이크로칩을 기반으로 하여 $5μl$의 시료만으로 PCR을 수행할 수 있도록 고안된, 휴대가 가능할 정도의 소형 GenSpector$^{TM}$ TMC-1000 PCR 기기를 이용한 새로운 기술이다. 본 연구에서 개발된 초고속 정량 PCR을 이용하였을 때 TYLCV 진단을 위한 30 cycle의 PCR과 용융점분석(melting curve analysis)에 15분 이내의 시간이 소요되었으며, GenSpector$^{TM}$ TMC-1000 PCR을 이용한 초고속 정밀진단 기술은 향후 TYLCV의 대발생을 모니터링하는데 유용하게 사용될 수 있을 것으로 생각한다. 본 연구결과는 GenSpector$^{TM}$ TMC-1000 PCR기반의 초고속정량 PCR 기술을 이용한 식물 바이러스의 진단기술 개발로는 최초의 보고이다.